A study of cardiovascular risk in dyslipidemia patients and role of statins in lowering the lipid levels. (World Journal of Current Medical and Pharmaceutical Research, 2025)
This study aimed to predict CVD risk in dyslipidemia patients based on factors like HTN, DM, hypothyroidism, alcohol, smoking, and obesity. We recruited 75 dyslipidemia patients (July–December 2023) and analyzed their CVD risk via 2D-ECHO & ECG. Statin combination therapy (Ecosprin, Ecosprin + Rosuvastatin) was prescribed for CVD-confirmed patients, while statin monotherapy (Atorvastatin) was given to those without CVD risk, aligning with Kirsten Bibbins-Domingo et al.'s study. Participants were categorized by age: 18–30 (11), 31–43 (17), 44–56 (22), and >56 (25). Gender-wise, females (40) outnumbered males (35), similar to Seyed Mahmoud Latifi et al.'s study. Based on residence, 47.67% were urban and 57.53% rural, with rural participants being higher.  HTN was found in 52 patients, with 34 at CVD risk. DM was present in 34, with 24 at risk, aligning with Razieh Anari et al.'s findings. Hypothyroidism affected 22 patients, with 11 at risk, similar to Fatima Tarboush et al.'s study. Obesity was noted in 24 patients, with 17 at risk. Alcohol consumption was reported in 36 patients, with 28 at risk, while 31 were smokers, with 23 at risk. These findings highlight significant CVD risk factors in dyslipidemia patients.